Synthesis of Pt Decorated ZIF-67-Derived Co–N–C Catalysts with Low Pt Contents and Increased Performance for Oxygen Evolution Reactions. (1st July 2022) - Parkash, Anand; Solangi, Nizamuddin; Aurangzeb, Junejo; Abbasi, Irfan Ahmed; Inam, Muhammad Ali; Soomro, Suhail Ahmed
Abstract : A significant step in commercializing zinc-air batteries is the development of a low platinum-group metal (PGM) concentration, high catalytic activity, and an effective electrocatalyst for the oxygen evolution process. A nitrogen-doped carbon stabilized Pt-Co bimetallic nanoparticle (Pt@Co-NC-900) with very low Pt content (2 wt%) was successfully produced using a metal-organic framework (MOF) templated technique. The as-developed Pt@Co-NC-900 demonstrates exceptional catalytic activity and long-term durability, exceeding commercial RuO2 catalysts and many previously reported catalysts with significant PGM content, attributed to its low overpotential of 223 mV. This research proposed a new approach for developing cost-effective and multifunctional catalysts using an N-containing MOF template.